THE EFFECT OF PURSED LIP BREATHING EXERCISE ON RESPIRATORY RATE IN PATIENT WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE: A CASE STUDY - Nurbaity, Annisa; Sari, Dwi Rosella Komala (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Chronic Obstructive Pulmonary Disease(COPD) is a chronic lung disease accompanied by airflow limitation that is not fully reversible. Airflow obstruction is generally progressive and is associated with an abnormal inflammatory response of the lungs to noxious particles or gases. The most common problems include chronic cough, increased sputum and shortness of breath. This increase in sputum and shortness of breath can affect changes in the respiratory rate of COPD patients. Case Presentations: A 55-year-old male patient complained of shortness of breath and cough. The patient works as a textile factory worker. The patient was diagnosed with COPD by a Lung Specialist and referred for physiotherapy to improve breathing patterns so that the respiratory rate returns to normal. Management and Outcomes: Effect of Pursed Lip Breathing Exercise to determine the respiratory rate in patient with Discussions: After physiotherapy intervention and evaluation were carried out, it was found that there was a decrease in the respiratory rate of 24 times per minute and T1: 19 times per minute. This happens because the pursed lip breathing exercise mechanism itself is a technique that focuses on expiration by deliberately inhibiting the shape of the lips that make it difficult for air to escape, thus requiring the help of diaphragm and abdominal muscle contractions to expel the air so that the volume of air will increase. Conclusion: After the physiotherapy session, the results showed that there was a The effect of pursed lip breathing exercise on respiratory rate in COPD patients is to provide a decrease in respiratory rate.